Comprehensive Analysis of AC and DC Capacitor Banks for UPS Applications - Tshepo Sithole; Vasudeva Rao Veerdhi; Thembelani Sithebe (International Journal of Electrical, Energy and Power System Engineering)
This paper reviews the use of large DC aluminum electrolytic and AC polymeric film capacitors within Uninterruptible Power Supply (UPS) applications, focusing on aspects such as field aging, failure mechanisms, anticipated service life, and preventative maintenance of capacitors. UPS systems are equipped with substantial capacitor banks comprising both DC electrolytic and AC polymeric film capacitors. Both types of capacitors undergo degradation under real-world operating conditions, with field aging being a gradual process that can span several years. The review highlights that implementing a proactive replacement plan for AC polymeric film and DC aluminum electrolytic capacitors can significantly improve the reliability and performance of UPS systems and extend their service life. This approach successfully helps organizations prevent downtime and enhance power supply stability, leading to greater operational efficiency.